2018
DOI: 10.1371/journal.pmed.1002671
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphate exposures during pregnancy and child neurodevelopment: Recommendations for essential policy reforms

Abstract: In a Policy Forum, Irva Hertz-Picciotto and colleagues review the scientific evidence linking organophosphate pesticides to cognitive, behavioral, and neurological deficits in children and recommend actions to reduce exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(86 citation statements)
references
References 34 publications
(42 reference statements)
1
84
0
1
Order By: Relevance
“…The irregular use, environmental contamination, human intoxication and imminent threat with chemical attacks are a current worldwide concern related to the chemistry of OPs. [1][2][3] Indeed, the extensive use of agrochemicals has raised the radar towards the development of reliable monitoring systems and destruction processes for unused stockpiles. Intrinsically related to this is the issue of chemical war.…”
Section: Introductionmentioning
confidence: 99%
“…The irregular use, environmental contamination, human intoxication and imminent threat with chemical attacks are a current worldwide concern related to the chemistry of OPs. [1][2][3] Indeed, the extensive use of agrochemicals has raised the radar towards the development of reliable monitoring systems and destruction processes for unused stockpiles. Intrinsically related to this is the issue of chemical war.…”
Section: Introductionmentioning
confidence: 99%
“…Pesticide exposures have been linked to several negative human health effects, such as asthma; cancer; and disruption of the nervous, endocrine, and reproductive systems [40][41][42][43][44][45][46]. Young children and pregnant women are particularly sensitive to pesticide exposures [5,7,[47][48][49][50][51], which have been linked to delays in human fetal development and lifelong neurotoxic disabilities [52][53][54][55][56]. Recognizing the risks posed by pesticide exposure highlights the need for further investigation into the underlying molecular mechanisms of action and evidence-based programs of prevention [57].…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that fetal development is the window of susceptibility for adverse effects of pesticide exposures, although work in this area is conflicting. In particular, the fetal brain is sensitive to toxicants due to rapid growth and development [5][6][7]. Previous studies have shown that OP and carbamate insecticides are neurotoxic due to inhibition of acetylcholinesterase (AChE), resulting in increased levels of the neurotransmitter acetylcholine in the synaptic cleft, impeding cholinergic neurotransmission [8].…”
Section: Introductionmentioning
confidence: 99%
“…The wide use of insecticides has raised a signi cant concern due to possible health effects associated with exposure to these compounds (Carvalho 2006;Dich et al 1997;Hertz-Picciotto et al 2018a;Hertz-Picciotto et al 2018b;Hertz-Picciotto et al 2018c). Insecticides are used globally to control crop pests in agriculture, to reduce household pests, to reduce insect damage to lawns and golf courses, and as mosquito control agents ( (EPA) 2000;Eaton et al 2008;Shelton et al 2012).…”
Section: Introductionmentioning
confidence: 99%